A Biomechanical Comparison of Successful and Unsuccessful Snatch Attempts among Elite Male Weightlifters - Hideyuki Nagao; Yasuyuki Kubo; Tempei Tsuno; Sho Kurosaka; Masato Muto (MDPI AG, 2019)
The success factor of the snatch has not been identified. Determining the success factors of the snatch among elite weightlifters might help to attain a successful snatch. This study aimed at clarifying the factors that lead to a successful snatch based on barbell trajectory among elite male weightlifters. Data were collected at the 2017 World and Junior World Weightlifting Championships. We digitized the barbell trajectory of the successful and unsuccessful snatch attempts of 61 lifters—an unsuccessful lift would be as a result of a frontward barbell drop—and calculated the kinematic and kinetic parameters of the barbell. No significant difference was found in the barbell maximum height (Dy1) between the successful and unsuccessful lifts. The amount of backward displacement of the barbell in the second pull phase to the catch position (DxL) of the successful lift was significantly larger than that of the unsuccessful lift (successful: 0.11 ± 0.05 m; unsuccessful: 0.10 ± 0.06 m; p < 0.01; d = 0.278). The barbell drop distance in the catch phase (Dy3) of the successful lift was significantly smaller than that in the unsuccessful lift (successful: 0.17 ± 0.04 m; unsuccessful: 0.18 ± 0.04 m; p < 0.001, d = 0.361). These results suggest that DxL and Dy3 are factors leading to a successful snatch lift, but not Dy1. The relative position in the sagittal axis of the barbell and the lifter in the catch position, and catching the barbell when its momentum was low, are important in order to achieve a successful snatch.